Partisipasi dan Swadaya Masyarakat dalam Rangka Menyukseskan Pamsimas III di Kabupaten Bungo, Provinsi Jambi - Asminar Asminar (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2019)
Clean water is essential for daily life. Using less appropriate water may cause variety of diseases, such as waterborne diarrhea, especially in rural areas. Pamsimas program, or community-based water supply and sanitation program, is government's program conducted in order to improve water supply, aiming to increase the coverage of water and sanitation services for decent and sustainable sanitation. The purpose of this research is to understand the level of community participation and self-support in improving universal access and to understand the influence of Pamsimas III program to the access of clean water in villages. Data used in this study are secondary data with descriptive analysis tools by observing community participation and community self-help in Pamsimas III program in Bungo Regency, Jambi Province. Simple correlation analysis was conducted to see the relation in community before and after the program. Menawhile, multiple linear regression analysis was conducted to see the relation between Pamsimas III program and the level of accessibility of clean water in Bungo Regency, Jambi Province. Results showed that community participation is very high in every stage of Pamsimas program. Community self-help in improving universal access is found very high beyond the requirements of Pamsimas program, which is proved by the presence of home channels. Pamsimas III program has high correlation with the accessibility of clean water in villages, with a correlation value of 0.992. The level of accessibility of Pamsimas III Program to the availability of high water is high with an R2 value of 0.815 or 81.5%.